2013
DOI: 10.1007/s11926-013-0396-1
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and Xanthine Oxidoreductase in Wound Healing

Abstract: Chronic wounds are an important health problem because they are difficult to heal and treatment is often complicated, lengthy and expensive. For a majority of sufferers the most common outcomes are long-term immobility, infection and prolonged hospitalisation. There is therefore an urgent need for effective therapeutics that will enhance ulcer healing and patient quality of life, and will reduce healthcare costs. Studies in our laboratory have revealed elevated levels of purine catabolites in wound fluid from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 82 publications
3
33
0
Order By: Relevance
“…Such inflammatory mediators play significant roles in inflammatory responses (Rider & Jordan, ; Zhao, Liang, Clarke, Jackson, & Xue, ). Furthermore, a study of 29 patients with CLUs by Fernandez, Upton, Edwards, Finlayson, and Shooter () found an increase in the level of uric acid in wound fluid was associated with increased severity of chronic venous leg ulcers (Fernandez et al, ; Fernandez, Upton, & Shooter, ). Thus, the current finding somewhat supports suggested links found in previous research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such inflammatory mediators play significant roles in inflammatory responses (Rider & Jordan, ; Zhao, Liang, Clarke, Jackson, & Xue, ). Furthermore, a study of 29 patients with CLUs by Fernandez, Upton, Edwards, Finlayson, and Shooter () found an increase in the level of uric acid in wound fluid was associated with increased severity of chronic venous leg ulcers (Fernandez et al, ; Fernandez, Upton, & Shooter, ). Thus, the current finding somewhat supports suggested links found in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Such inflammatory mediators play significant roles in inflammatory responses (Rider & Jordan, 2010;Zhao, Liang, Clarke, Jackson, & Xue, 2016). Furthermore, a study of 29 patients with CLUs by Fernandez, Upton, Edwards, Finlayson, and Shooter (2012) found an increase in the level of uric acid in wound fluid was associated with increased severity of chronic venous leg ulcers (Fernandez et al, 2012;Fernandez, Upton, & Shooter, 2014 Table 4). However, due to the limitation of small sample size and/ or the difference in the sample characteristics, two of the previously identified factors, depression and calf-ankle circumference ratio <1.3, were not able to be included in this multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previous NZ research, infection was found to be a common cause for admission in those with gout. Recent work has suggested that urate may play a role in wound healing and potentially have wider impacts on inflammation …”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate scavenging of these ROS generally results in a delay of wound healing, individuals with chronic leg ulcers and lesions due to ischemia present excessive production of oxygen radicals with significant xanthine oxidase activity [40].…”
Section: Discussionmentioning
confidence: 99%